2014
DOI: 10.1021/jf405773b
|View full text |Cite
|
Sign up to set email alerts
|

Novel Strategy To Create Hypoallergenic Peanut Protein–Polyphenol Edible Matrices for Oral Immunotherapy

Abstract: Peanut allergy is an IgE-mediated hypersensitivity. Upon peanut consumption by an allergic individual, epitopes on peanut proteins bind and cross-link peanut-specific IgE on mast cell and basophil surfaces triggering the cells to release inflammatory mediators responsible for allergic reactions. Polyphenolic phytochemicals have high affinity to bind proteins and form soluble and insoluble complexes with unique functionality. This study investigated the allergenicity of polyphenol-fortified peanut matrices prep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 68 publications
3
53
2
Order By: Relevance
“…The shifts observed indicated the development of interactions between CS and PNPs functional groups. Amide II around 1535 cm −1 (Plundrich et al, 2014) appeared for CS films with 1, 2, and 4% PNPs, what is more, the increase in the absorption signal could be observed with the increasing of PNPs content. These results evidenced the compatibility of both polymers.…”
Section: Fourier Transform Infrared Spectra Of Cornstarch Nanocomposimentioning
confidence: 78%
“…The shifts observed indicated the development of interactions between CS and PNPs functional groups. Amide II around 1535 cm −1 (Plundrich et al, 2014) appeared for CS films with 1, 2, and 4% PNPs, what is more, the increase in the absorption signal could be observed with the increasing of PNPs content. These results evidenced the compatibility of both polymers.…”
Section: Fourier Transform Infrared Spectra Of Cornstarch Nanocomposimentioning
confidence: 78%
“…Nitroblue tetrazolium and glycine were purchased from Sigma-Aldrich (Sigma-Aldrich, St. Louis, MO, USA). All other SDS-PAGE and immunoblotting reagents used are listed elsewhere 3 . Egg white protein (EWP) was purchased from Sigma-Aldrich (St. Louis, MO, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Samples (10 µg protein/10 µL) were incubated for 5 min at 95°C, loaded onto a gel, run (40 min at 200 V), and then stained with Coomassie Brilliant Blue (CBB). The immunoblotting method used, including reagent sources, is described elsewhere 3 . The following minor modifications were made: Pooled human plasma (containing polyclonal antibodies, among them egg white-specific IgE) from 7 egg white-allergic individuals (PlasmaLab International, Everett, WA, USA; 1:80; v/v) was used to bind antigens on the membrane.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypoallergenic formulas based on hydrolyzed milk proteins for infants with cow's milk allergy are commercially available since 1985. Recent laboratory studies have shown potential hypoallergenicity of peanut-polyphenol edible matrix [62] and cashew allergens treated with sodium sulfite in a temperature-dependent manner [63].…”
Section: Allergen Detectionmentioning
confidence: 99%